2022
DOI: 10.3390/sports10070100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-Week of FIFA 11+ Warm-Up Program on Explosive Strength, Speed, and Perception of Physical Exertion in Elite Female Futsal Athletes

Abstract: Futsal is a sport that originates from soccer and is increasingly practiced all over the world. Since training and warm-up protocols should be sport-specific in order to reduce injuries and maximize performance, this study aimed to evaluate the effects of 5 weeks of the FIFA 11+ warm-up program on explosive strength, speed, and perception of physical exertion in elite female futsal athletes. Twenty-nine elite female futsal athletes participating in the Italian national championships were divided into two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In a study, Chtorou et al [2] found that power output increased in male sprinters during the 30-s Wingate Anaerobic Test (WAnT) after a 10-min warm-up with and without music. It has been reported in many exercises in the literature that methods such as warm up, stretching, music and visual feedback before competitions and training are necessary to improve athletic performance [2,[5][6][7][8][9][10]. Pre-exercise warm-up, a common technique, is defined as necessary to maximize the athlete's performance in a variety of sports and physical activities by changing the body's physiological mechanisms (muscle temperature, nerve conduction velocity, increased blood flow).…”
Section: Introductionmentioning
confidence: 99%
“…In a study, Chtorou et al [2] found that power output increased in male sprinters during the 30-s Wingate Anaerobic Test (WAnT) after a 10-min warm-up with and without music. It has been reported in many exercises in the literature that methods such as warm up, stretching, music and visual feedback before competitions and training are necessary to improve athletic performance [2,[5][6][7][8][9][10]. Pre-exercise warm-up, a common technique, is defined as necessary to maximize the athlete's performance in a variety of sports and physical activities by changing the body's physiological mechanisms (muscle temperature, nerve conduction velocity, increased blood flow).…”
Section: Introductionmentioning
confidence: 99%
“…Still, the idea behind it is that the warm-up should include some features that promote neuromuscular readiness that will be required later in the training session (or competition) [ 9 , 27 ]. Of note, this feature would suggest that warm-ups should be specific instead of general (i.e., mimicking some demands of the sport) [ 28 30 ]. Things are more complex than that, and this topic will be discussed further below.…”
Section: What Is the Warm-up Used For?mentioning
confidence: 99%
“…Anaerobic-based explosive movements related to basketball can be categorized into high-intensity activities requiring jumping, change of direction (COD), running speed, and acceleration/deceleration [ 1 , 2 , 3 ]. Such movement patterns in explosive form require a high level of lower-extremity power [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%